2002
DOI: 10.1080/03085140220151837
|View full text |Cite
|
Sign up to set email alerts
|

The effects of convergence: internationalization and the changing distribution of net value added in large German firms

Abstract: The paper examines whether and how the increasing internationalization of rms impacts on the operation of a co-ordinated market economy. Following the tenets of agency theory, it assumes that an emerging market for corporate control changes the monitoring mechanisms that oversee management. Since Anglo-American forms of monitoring are usually associated with a higher return for investors compared with Continental European rms, a change in the distribution of the net value added of rms is expected. Using nancia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…In an IB-based study of 150 corporations from the UK, Germany, and Canada, Bondy et al (2004Bondy et al ( , 2008 found evidence of some convergence of the German national business system model [i.e., the network-oriented model of ''Rhenish capitalism,'' (Albert, 1991)] toward the UK's ''Anglo-Saxon model of marketoriented shareholder capitalism.'' Similarly, Beyer and Hassel (2002), in a study examining the 100 largest companies in Germany from 1992 to 1998, revealed the emerging convergence of German corporate governance practices with Anglo-Saxon standards, guided by legal changes that encouraged the transparency and liberalization of financial markets. Nonetheless, Beyer and Hassel's study found no evidence of convergence in the relationship between management and employees.…”
mentioning
confidence: 94%
“…In an IB-based study of 150 corporations from the UK, Germany, and Canada, Bondy et al (2004Bondy et al ( , 2008 found evidence of some convergence of the German national business system model [i.e., the network-oriented model of ''Rhenish capitalism,'' (Albert, 1991)] toward the UK's ''Anglo-Saxon model of marketoriented shareholder capitalism.'' Similarly, Beyer and Hassel (2002), in a study examining the 100 largest companies in Germany from 1992 to 1998, revealed the emerging convergence of German corporate governance practices with Anglo-Saxon standards, guided by legal changes that encouraged the transparency and liberalization of financial markets. Nonetheless, Beyer and Hassel's study found no evidence of convergence in the relationship between management and employees.…”
mentioning
confidence: 94%
“…This may be a surprise, as shareholder-oriented restructuring promotes profitability by slowing down growth and therefore amounts to redistribution away from employees (Beyer and Hassel, 2002). Several mechanisms help works' councils tolerate the introduction of profitability goals and restructuring.…”
Section: Shareholder Orientation and Industrial Relations In Germanymentioning
confidence: 99%
“…The dissolution of the German company network, both in terms of interlocking capital and interlocking directorates, had been under way since around 1985 and accelerated dramatically after 1995. Beyer and Hassel (2002) have shown that the increased shareholder orientation of German companies resulted in a reorientation of companies from growth to profitability, and as a consequence in a re-distribution of net value added to shareholders from employees.…”
Section: Shareholder Orientation and Industrial Relations In Germanymentioning
confidence: 99%
See 1 more Smart Citation
“…11 This increased unemployment and exacerbated the financial problems of the social security and pension system, as many companies reduced the number of employees via early retirement schemes. Especially important is the reduced willingness of companies following shareholder value principles to keep employment constant in times of economic crisis.…”
Section: Corporate Governance and Organised Capitalismmentioning
confidence: 99%